Changes in Collagen Structure and Permeability of Rat and Human Sclera After Crosslinking - Guo, Peng (Transl Vis Sci Technol, 2020)
PURPOSE: To use second harmonic generation imaging and fluorescence recovery after photobleaching to demonstrate alterations in scleral collagen structure and permeability after crosslinking in rat and human eyes. METHODS: Excised rat and human scleras were imaged ex vivo with an inverted two-photon excitation fluorescence microscope before and after photochemical crosslinking using riboflavin and 405-nm laser light. Fluorescence recovery after photobleaching was applied to measure the diffusion of fluorescein isothiocyanate–dextran across the sclera. RESULTS: Crosslinking caused scleral collagen fibers to become wavier and more densely packed, with surface collagen being more affected than deeper collagen fibers. Crosslinked sclera showed significantly decreased permeability in the irradiation zone and also extended as far as 250 µm outside the irradiation zone. CONCLUSIONS: Photochemical crosslinking induced changes in scleral structure and permeability that extended to tissue even outside the irradiation zone. TRANSLATIONAL RELEVANCE: Ultrastructural changes associated with the emerging clinical technique of photochemical scleral crosslinking have not been well characterized. We demonstrate not only changes in scleral collagen by second harmonic generation imaging but also the associated functional changes in tissue permeability by fluorescence recovery after photobleaching. We report the novel finding of reduced permeability extending well beyond the direct irradiation zone. This has implications for control in the clinical setting.